Determining the location of a distribution centre using centre search based on employment data - Schein, Péter; Skapinyecz, Róbert (Advanced Logistic Systems - Theory and Practice, 2026)
Urban freight transport presents significant challenges to the goals of sustainable mobility and energy efficiency. The aim of this paper is to provide an approach utilizing center search and employment data for selecting the optimal location of a distribution center designed for electrified urban freight transport. The application of the proposed method is demonstrated through a case study, in which a potential site for a logistics center in and around Miskolc was identified, using multiple center search methods such as area grids and radial models. The paper also presents additional practical results, including the required fleet size and the characteristics of the supply area. The findings highlight that with thorough planning and appropriate data collection, a logistics center can significantly improve the efficiency and environmental performance of freight transport.